Evaluación del comportamiento mecánico de adoquines con adición de plástico reciclado para pavimento articulado vehicular (2023)
The addition of recycled materials as an alternative to improve the mechanical behavior of products for the construction of civil works has become a permanent research, either to lighten them or to improve their resistance. In this research, additions of recycled shredded tire mesh 30 (M 30 - 0.6mm), mesh 25 (M 25 - 1.0 mm), mesh 10 (M 10 - 2.0 mm) and mesh 5 (M 5 - 4.0 mm) are used, also additions of high density polyethylene are used in presentation of recycled plastic, complying with the SDGs (Sustainable Development Goals). For this purpose, a step-by-step approach was proposed, gathering essential research information at national and international level related to additions of the same, regulations and technical and quality compliance, characterization of materials was made under current standards such as NTC 2017 and dosage is proposed according to ACI 211 methodology. 1, establishing minimum compliance parameters for concrete with a resistance of 21 MPa, as in this case for paving blocks for vehicular articulated pavements, in such a way that it complies with the setting time and the elaborated elements obtain the design resistance, to be failed in compression; then make the comparison with paving blocks without additions and determine if it complies with the technical and quality conditions to be a competitive product as a new alternative for the construction or improvement of roads with difficulty of entry or transit of light and heavy traffic